Strategi Public Relations Thursina International Islamic Boarding School Malang Dalam Mendukung Program Pendaftaran Calon Santri “Pass and Priority Program” - Amalia Amira Nur Rohma; Syifa Syarifah Alamiyah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Education in Indonesia, especially Islamic-based ones, is experiencing rapid development with the boarding school system. Thursina IIBS is one of the educational institutions that has succeeded in combining religious and general education with a holistic and balanced approach. Indent enrollment in an educational context allows schools to predict enrollment numbers and plan required resources more effectively. Through the Pass and Priority Program, prospective students can register long before entering education at Thursina IIBS, giving them time to prepare themselves. Even though this program attracts the interest of many prospective student guardians, the challenges faced by Thursina IIBS are not easy. One of the main challenges is how to maintain the interest and commitment of prospective students and student guardians during this long waiting period. In this context, the role of Public Relations becomes very important. The aim of the research carried out is to analyze how the Thursina IIBS public relations team maintains good relations with prospective student guardians during the waiting period for pivot registration. The method used in this research is qualitative research and data collection is carried out by means of observation, interviews, documentation. The research results show that the public relations strategy implemented by Thursina IIBS in the "Pass and Priority" program was successful in retaining the majority of prospective students and guardians of students during the long waiting period. Even though there were applicants who withdrew, the majority remained, which shows that the communication approach, personal service, coaching program, and use of digital media have succeeded in creating trust and loyalty among prospective student guardians.